A Buddhist perspective on death: An ethnographic study and implications for nonprofit marketing in grief support and terminal illness. Issue 1 (21st December 2016) - Choudhury, Koushiki
Abstract : The liminal state associated with terminal illness and death of a loved one is characterized by a marginalized experience, often accompanied by immense grief, confusion, isolation, and in cases identity crisis. There exists a range of issues that make marketing to these groups very different from marketing to non‐sensitive segments. This paper adds to the literature on marketing to sensitive groups by exploring the concept of death and implications for nonprofit organizations in grief support and terminal illness, with an ethnographic study of one of the world's largest Nichiren Buddhist organizations. It shows that Buddhist concepts of death can play a compassionate role for nonprofit organizations in countering the delusory fear and hopelessness of death for families and patients coping with bereavement and imminent death.